Public procurement in the U.S. Federal government and the European Union: hidden non-tariff barriers - Schoeni, Daniel (2023)
This work imagines a hypothetical in which the Transatlantic Trade and Investment Partnership (TTIP) has been enacted and de jure barriers to the public procurement markets in the US federal government and the EU Member States have been removed. It considers what non-tariff barriers would endure based on the US’s and the EU’s divergence of laws and ‘embedded legal cultures’. These remaining barriers, it argues, would be significant. To remove such de facto barriers, the first step is to understand them. Employing an extended thought experiment about what barriers a European supplier would find in US federal procurement and an American supplier would find when selling to Member States (viewing them from an aggregated, ‘unified European outlook’), it attempts to deepen mutual understanding of the two systems and to encourage further research. Of a secondary benefit, such an analysis may help us to see better what is in front of our noses.